Safety of Electro-Convulsive Therapy in Combination with Duloxetine in Treatment-resistant Depressive Patients: A Randomized Clinical Trial - Fakhraei, Bahareh; Farjam, Mojtaba; Moghimi Sarani, Ebrahim; Samimi, Nastaran; Hedayati, Arvin; Jaafari, Nematollah (Galen Medical Journal, 2022)
Background: There are several strategies in the management of treatment-resistant depression (TRD), including the administration of other antidepressants, augmentation therapy, electro-convulsive therapy (ECT), and a combination of ECT and antidepressants. The safety of ECT combined with any medication must be confirmed. The aim of this study was to assess the safety of duloxetine and ECT combination therapy. Materials and Methods: In this randomized clinical trial, the probable side effects of ECT plus duloxetine were compared with ECT plus sertraline in two groups of admitted TRD patients. Patients with general medical diseases and/or any contraindications to ECT or any of the two drugs were excluded. General side effects, including nausea, vomiting, and headache reported by patients (hours after ECT) as well as cardiotoxicity by electrocardiogram (immediately after any ECT episode), cognitive status by mini-mental state examination (MMSE, one month after the last ECT), and seizure duration were recorded for each patient. Results: No significant differences were observed in nausea, vomiting, headache, and myalgia between ECT+duloxetine and ECT+sertraline groups. Heart rate, QTc interval, ST-T change, and the incidence of arrhythmia were the same between the two arms of the study. Also, no prolonged seizures and status epilepticus were recorded among the studied patients. The MMSE revealed no marked differences in the cognitive status among patients of the two groups. Conclusion: ECT+duloxetine and ECT+sertraline were equally safe in patients with TRD.